Life Satisfaction in relation to Happiness: Examining the Relationship between Life Satisfaction and Happiness in Adolescents (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Life satisfaction is a global assessment of a person‟s life according to his chosen criterion.Happiness play important role in life satisfaction. The aim of the present study was to study the correlationbetween life satisfaction and happiness. A sample of 100 adolescents (class eleven and twelfth students)were taken for the present purpose. Data was analyzed by Pearson correlation and independent sample ttest.Results of the study indicate that males are significantly higher than female on life satisfaction.Results of study also show that there is no significant difference between male and female on happiness.Life satisfaction is found positively and significantly correlated with happiness.